EVALUATION OF OPTIMAL ECOLOGICAL TOURISM ROUTES OBTAINED VIA GOOGLE EARTH SOFTWARE IN AN ENVIRONMENTAL PROTECTION AREA - Araújo Júnior, Carlos Alberto; Miranda, Paulo Ricardo Santos; Gonçalves, Thais Sales; Zuba, Sthefany Mendes; Castro, Renato Vinícius Oliveira; Marcatti, Gustavo Eduardo (Floresta, 2021)
Ecological tourism stands out as an economic activity that can be reconciled with nature conservation. Such activities have been carried out in several conservation units in Brazil. However, for satisfactory implementation, it is necessary to effectively plan the activities to be conducted, places to be visited, and paths to reach those places. In this context, we aimed to assess whether Google Earth software can assist in the expansion of the plan to use these areas for ecotourism, especially the routes that may be taken by tourists within the conservation unit. For this purpose, tourist interest sites were defined in the State Environmental Protection Area of Rio Pandeiros in the northern region of the state of Minas Gerais. The shortest routes between the pairs of locations obtained using Google Earth and QGIS software were evaluated. Additionally, it was necessary to perform vectorization and classification of all roads in the area. The lengths of the paths obtained were compared using a method identity test. The results showed that for most routes, Google Earth showed longer paths than QGIS. It can be concluded that for the purpose of ecotourism, precise planning should consider the vectorization of roads in areas with many rural roads.